Bacterial Reverse Mutation Test of Verbenalin - Hye Jeong Shin; Yi Gun Lim; Ji Su Ha; Gabsik Yang; Tae Han Yook (Korean Pharmacopuncture Institute, 2022)
Objectives: Verbenalin is a compound found in herbs such as Cornus officinalis and Verbena officinalis. This study investigated whether verbenalin is safe by analyzing its mutagenicity. Methods: To examine the mutagenic potential of verbenalin, a bacterial reverse mutation test (Ames test) was conducted with Salmonella typhimurium and Escherichia coli strains. Experiments with and without metabolic activity were performed.Results: The mean colony number was less than double that of the control. Growth inhibition and precipitation of verbenalin were not apparent in all strains at different concentrations regardless of metabolic activity.Conclusion: Verbenalin did not show any signs of mutagenicity in this study. Additional toxicity studies including repeated oral toxicity, reproductive toxicity, and carcinogenicity tests are needed.